2010
DOI: 10.4103/0974-8520.72361
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ghee (clarified butter) on serum lipid levels and microsomal lipid peroxidation

Abstract: Ghee, also known as clarified butter, has been utilized for thousands of years in Ayurveda as a therapeutic agent. In ancient India, ghee was the preferred cooking oil. In the last several decades, ghee has been implicated in the increased prevalence of coronary artery disease (CAD) in Asian Indians due to its content of saturated fatty acids and cholesterol and, in heated ghee, cholesterol oxidation products. Our previous research on Sprague-Dawley outbred rats, which serve as a model for the general populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 32 publications
4
64
1
Order By: Relevance
“…[24][25] Ghee contains fat which function as a structural element of the cell and is a major source of energy. 26 Ghee contains medium chain triglycerides which are immediate source of energy. MCT improves the metabolic rate, spare the muscle glycogen and improves physical endurance performance.…”
Section: Observations and Resultsmentioning
confidence: 99%
“…[24][25] Ghee contains fat which function as a structural element of the cell and is a major source of energy. 26 Ghee contains medium chain triglycerides which are immediate source of energy. MCT improves the metabolic rate, spare the muscle glycogen and improves physical endurance performance.…”
Section: Observations and Resultsmentioning
confidence: 99%
“…According to Ayurveda, ghee protects the body from various diseases and promotes longevity. Its lubricating action helps in reducing pain of mouth ulcer [18].…”
Section: Discussionmentioning
confidence: 99%
“…Soyabeen Oils and canola oils have been found to contain toxic trans fats as high as 4.2% (O' Keefe, 1994). A high omega-6 to omega-3 ratio has been linked to depression and inflammatory diseases (Kiecolt-Glaser et al, 2007) Desi ghee: A study on desi ghee on rats (for both the heated and native ghee) found a significant decrease in serum total cholesterol levels, a decrease of 20-25% in serum triglycerides, a 14-16% decrease in liver total cholesterol levels, a 14-29% decrease in liver triglyceride levels (Sharma et al, 2010). Preparation of ghee by traditional ayurvedic method contains higher amount of DHA.…”
Section: Issues and Concernsmentioning
confidence: 99%